Extreme cultural persistence in eastern-central Brazil: the case of Lagoa Santa Paleaeoindians - ASTOLFO G.M. ARAUJO (Anais da Academia Brasileira de Ciências)
ABSTRACT Lapa do Santo rockshelter, a Paleoindian site located in Eastern-Central Brazil, presented two main occupations; one during Early Holocene (12,460 to 8700 cal BP), and a latter in Middle Holocene (5100 to 4200 cal BP). In spite of this 3600 year gap, the stratigraphy and general characteristics of the material culture did not indicate any visible discontinuity. This led us to hypothesise a reoccupation of the rockshelter by the same cultural group, tested by means of statistical analyses comparing lithics, bone artifacts, and faunal remains from early and middle Holocene layers. No significant differences were found, and our results indicate the presence of a cultural tradition that persisted for 8240 years, or roughly 412 generations.